Product Development Strategy PT. Pindad in Improving the Indonesian Defence Industry - Prahasto, Barkah Ardianto (IJOSMAS, 2023)
PT. Pindad is an Indonesian Manufacturing Industry Company which is engaged in Military Products and Commercial Products. Activities of PT. Pindad covers Design and Development, Engineering, Assembling, and Fabrication and Maintenance. This company is the only BUMN (State Owned Enterprise) company in Indonesia that is engaged in the military. The purpose of this research is the product development of PT. Pindad for the development of the Indonesian defence industry uses the Analytical Hierarchy Process (AHP) method with a sectorial approach. The sectorial approach is focused on the activity sectors in PT. Pindad. Based on research results from data related to the Indonesian defence industry, there are 4 superior products of the defence industry, including rifles, munitions, personnel transportation vehicles / armoured vehicles and medium tanks. By knowing some of the leading sectors, it can be expected to be the basis for the formulation of the defence industry to be free from dependence on supply of weapons systems from other countries and also free to determine foreign policy without being influenced by foreign pressure. Therefore, the Indonesian defence industry must be maintained and developed to increase Indonesia's status in the eyes of the world and strengthen our foreign diplomacy, especially defence diplomacy